Winning Hearts and Minds : representations of the Malay in the films of British Malaya / Hassan Abd Muthalib - Abd Muthalib, Hassan (UPENA, 2008)
Traditional entertainment for the Malays in the Malay Archipelago first came in the form of the Malay shadow play. It was nothing more than light entertainment meant for the ordinary Malay to recuperate after a hard day's work in the fields. More light entertainment, this time with song and dance, then appeared with Malay opera and Malay theatre. When Malays stepped into film (beginning in Singapore in 1933), the same fare and presentation was literally transferred onto the screen. Song and dance became one of the pleasures that the Malay looked forward to in films and soon it became a sine qua non for every film.